Behavioral Biomarkers for Animal Health: A Case Study Using Animal-Attached Technology on Loggerhead Turtles - Arkwright, Alexandra C.; Archibald, Emma; Fahlman, Andreas; Holton, Mark D.; Crespo-Picazo, Jose Luis; Cabedo, Vicente M.; Duarte, Carlos M.; Scott, Rebecca; Webb, Sophie; Gunner, Richard M.; Wilson, Rory P. (Frontiers in Ecology and Evolution, 2020)
Vertebrates are recognized as sentient beings. Consequently, urgent priority is now being given to understanding the needs and maximizing the welfare of animals under human care. The general health of animals is most commonly determined by physiological indices e.g. blood sampling, but may also be assessed by documenting behaviour. Physiological health assessments, although powerful, may be stressful for animals, time-consuming and costly, while assessments of behaviour can also be time-consuming, subject to bias and suffer from a poorly defined link between behaviour and health. However, behaviour is recognized as having the potential to code for stress and well-being and could, therefore, be used as an indicator of health, particularly if the process of quantifying behaviour could be objective, formalized and streamlined to be time efficient. This study used Daily Diaries (DDs), (motion-sensitive tags containing tri-axial accelerometers and magnetometers), to examine aspects of the behaviour of bycaught loggerhead turtles, Caretta caretta in various states of health. Although sample size limited statistical analysis, significant behavioural differences (in terms of activity level and turn rate) were found between ‘healthy’ turtles and those with external injuries to the flippers and carapace. Furthermore, data visualization (spherical plots) clearly showed atypical orientation behaviour in individuals suffering gas emboli and intestinal gas, without complex data analysis. Consequently, we propose that the use of motion-sensitive tags could aid diagnosis and inform follow-up treatment, thus facilitating the rehabilitation process. This is particularly relevant given the numerous rehabilitation programs for bycatch sea turtles in operation. In time, tag-derived behavioural biomarkers, TDBBs for health could be established for other species with more complex behavioural repertoires such as cetaceans and pinnipeds which also require rehabilitation and release. Furthermore, motion-sensitive data from animals under human care and wild conspecifics could be compared in order to define a set of objective behavioural states (including activity levels) for numerous species housed in zoos and aquaria and/or wild species to help maximize their welfare.